Pengembangan Media Interaktif Berbasis Model Pembelajaran Guided Inquiry Pada Mata Pelajaran Simulasi Digital - Zulfahmi Lutfi; Riana T. Mangesa; Hendra jaya (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2023)
This study aims to determine (1) The results of developing interactive media based on guided inquiry. learning models in digital simulation subjects; (2) the effectiveness of using interactive media based on guided inquiry. learning models to foster student interest and learning activities; (3) The practicality of using interactive media based on guided inquiry. learning models in digital simulation subjects. This research is a type of Research and Development (R&D) research with the ADDIE development model which consists of several stages, namely analysis, design, development, implementation and system evaluation. The data analysis technique used is descriptive analysis. The subjects of this research product trial were 2 learning media experts, 1 material expert, 3 teachers and 35 students of SMK Nasional Makassar City. Data collection techniques in this study used observation, documentation and questionnaires. The results showed that the development of interactive media based on the quided inquiry learning model can motivate students to learn independently, creatively, effectively and efficiently with an assessment of the elements of validity given by media experts, which is an average of 4.74. Then the material expert gives an average assessment of 4.81, the average on each of these results is greater than the median Likert scale. Thus it can be said that learning media based on the quided inquiry learning model is very feasible to use. then in the element of effectiveness given by 3 teachers in the field trial, the average was 4.69 and for the large-scale trial of 35 students got an average of 4.70.The average of each result is greater than the median of the Likert scale.Thus it can be said that learning media based on the quided inquiry learning model is very effective.Then in the element of practicality given by 3 teachers in the field trial, the average was 4.76 and for the large-scale trial of 35 students got an average of 4.81.The average of each result is greater than the median of the Likert scale.Thus it can be said that learning media based on the quided inquiry learning model is very practical.